Fiscal policies in a monetary union: the eurozone case - Gennaro Zezza (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
We argue that the institutional framework of the eurozone was designed to deny a role for fiscal policy. However, the Great Recession of 2008–2009 forced governments to intervene, mainly to avoid the collapse of their financial systems. At the same time, the severe recession implied a decrease in tax revenues, and an increase in some components of public expenditure – such as unemployment benefits, which implied an increase in public deficits. When the crisis seemed to be over, the Maastricht rules gave priority to restoring fiscal targets, even at the cost of prolonged unemployment and stagnation in countries like Greece and Italy. Using the three-balances approach pioneered by Godley, we argue that such policies require the achievement of an external surplus, or else fiscal austerity will worsen the financial position of the private sector. We show that this is indeed how most eurozone countries moved, and argue that such policies are fragile, and possibly not sustainable in the medium term. We suggest the introduction of fiscal currencies as one way of introducing a degree of freedom in the sustainability of the eurozone.
Keywords: E62; F41; F45; 330; fiscal policy; monetary union; eurozone; austerity; sectoral balances